(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This study presents a novel approach to enhance facial analysis by integrating facial featuredescriptors and facial action unit (FAU) intensity detection using MultiView Distance Metric Learning(MV-DML). Recognizing and understanding facial expressions play a crucial role in human-computerinteraction, affective computing, and various applications in computer vision. To achieve more accurateand robust results in facial analysis, we propose a unified framework that fuses the information from twokey components facial feature descriptors and FAU intensity detection.Our approach leverages the power of MV-DML, which simultaneously learns optimal featurerepresentations for facial feature descriptors and FAU intensity labels. This enables the model to capturecomplex relationships between facial features and FAUs, leading to improved accuracy in expressionrecognition and intensity estimation. The learned distance metric facilitates a more comprehensiveunderstanding of the intricate facial dynamics, making it suitable for various applications, includingemotion recognition, human behavior analysis, and human-computer interaction.This study presents an innovative approach to enhance facial analysis by unifying facial featuredescriptors and FAU intensity detection through MultiView Distance Metric Learning. This approach hasthe potential to impact a wide range of applications, including those in the domains of affectivecomputing, human-robot interaction, and psychological research.